Screening of Antibiotic producing Actinomycetes for Antibiosis from soil of Sunsari, Nepal - Limbu, Dhiren Subba; Majhi, Ramesh; Sah, ShivNandan; Bantawa, Kamana; Rai, Bishan (Himalayan Journal of Science and Technology, 2023)
Actinomycetes, slow-growing gram-positive bacteria, are useful in the search for bioactive compounds. A total of 24 different actinomycete strains were recovered from farming soil samples collected from the Sunsari district. The isolates were then tested against two gram-positive and three gram-negative bacteria. Results showed that 21% of all isolates are antibacterial at least, one of the test organisms, Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Salmonella Typhi, and Pseudomonas spp. According to antibacterial activity and spectrum broadness, one of the isolates (S11) was selected for secondary screening. The minimum inhibitory concentration (MIC) of crude antibacterial substances extracted from the broth culture of the isolate (S11) was found to be 1.3 mg/ml against test organisms. The chromatogram in TLC showed only one spot with an Rf value of 0.87 by the isolate suggesting that the isolate produced only one compound which was utterly different from the spot with an Rf value of 0.94 paid by gentamycin. According to identification by Microscopy (1000X) and overall biochemical, and physiological characteristics, the isolate was considered Streptomyces antibioticus, a distinct taxonomic group.